2020
DOI: 10.1101/2020.07.08.193334
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mesoscale brain dynamics reorganizes and stabilizes during learning

Abstract: Adaptive behavior is coordinated by neuronal networks that are distributed across multiple brain regions. How cross-regional interactions reorganize during learning remains elusive. We applied multi-fiber photometry to chronically record simultaneous activity of 12-48 mouse brain regions while mice learned a tactile discrimination task. We found that with learning most regions shifted their peak activity from reward-related action to the reward-predicting stimulus. We corroborated this finding by funct… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Next, we discuss related research in Functional Connectivity (FC) [33] and Effective Connectivity (EC) [39], and highlight potential implications of our results on estimation of related metrics. Metrics of FC and EC aim to estimate a matrix of pairwise connections between variables (also known as functional connectome [29]), to test if individual connections are significant, to describe the connectivity matrix by means of integral metrics of network neuroscience [7], and to study changes in network connectivity associated for example with learning [6, 73, 74] or disease [14]. Redundancy is a well-known problem in this field as well.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Next, we discuss related research in Functional Connectivity (FC) [33] and Effective Connectivity (EC) [39], and highlight potential implications of our results on estimation of related metrics. Metrics of FC and EC aim to estimate a matrix of pairwise connections between variables (also known as functional connectome [29]), to test if individual connections are significant, to describe the connectivity matrix by means of integral metrics of network neuroscience [7], and to study changes in network connectivity associated for example with learning [6, 73, 74] or disease [14]. Redundancy is a well-known problem in this field as well.…”
Section: Discussionmentioning
confidence: 99%
“…As past and present of the target come from the same signal, the impurity fractions of both of these variables in real data are equal or almost equal, significantly reducing the possible magnitude of false positive unique information atoms. In another study [74], we validated the performance of transfer entropy in the presence of noise for simulated neuronal recordings. We found that the metric was able to correctly reject false positives within a range of low impurity fractions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations